Costly grace according to Dietrich Bonhoeffer: Why does it still matter today? - Saragih, Jan Christian Wismar (Institut Agama Kristen Negeri Toraja, 2025)
This article aims to explore the meaning of costly grace according to Dietrich Bonhoeffer and why it still matters for believers today in Indonesia. Throughout his exploration and interpretation, Bonhoeffer has written extensively about what he thought to be a costly grace to fight against cheap grace. Costly grace is also an idea that has been discussed by various theologians. Many have debated what it truly means from different perspectives. So, the question is, what does costly grace mean for Christians today? Bonhoeffer’s concept of costly grace has led theologians around the world to rethink what it means to have faith, precisely because Bonhoeffer’s version of faith itself is a costly one. Faith is also something that’s considered a great commitment that all Christians must have. Faith and grace themselves should not be cheap, and they should be costly. Bonhoeffer’s concept of costly grace is also worth considering in today’s world. This article finds that costly grace is needed for Christians today.